2020
DOI: 10.1111/aogs.13803
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of endometriosis with laparoscopy and near‐infrared optics with indocyanine green

Abstract: Introduction:Endometriosis is a common health problem, affecting 10% of women of reproductive age. Laparoscopic surgery is proven to relieve pain and to improve fertility in women with endometriosis. However, identifying peritoneal endometriosis lesions may be difficult due to their polymorphic aspects. Endometriosis lesions harbor a high degree of neovascularization. The visualization of tissue perfusion by the additional use of near infrared fluorescence imaging with indocyanine green (ICG) may improve the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(52 citation statements)
references
References 26 publications
1
51
0
Order By: Relevance
“…Conversely, Siegenthaler et al 8 and Lier et al 15 showed no advantage for NIR fluorescence imaging with ICG. Indeed, in their pilot study of 63 patients, Siegenthaler et al 8 reported a sensitivity of NIR‐ICG of 14.7%, very different from that found by Cosentino 11 and Vizzielli, 12 whose sensitivity was 82%. This inhomogeneity is difficult to interpret: in the two papers, the substantial differences concern the percentage of patients with previous surgery for endometriosis, 54% for Siegenthaler 8 and 44% in Cosentino’s work 11 and the fluorescence display time, which varies for the Siegenthaler between 2 and 20 minutes and for Cosenti between 5 and 30 minutes.…”
Section: Discussionmentioning
confidence: 78%
See 4 more Smart Citations
“…Conversely, Siegenthaler et al 8 and Lier et al 15 showed no advantage for NIR fluorescence imaging with ICG. Indeed, in their pilot study of 63 patients, Siegenthaler et al 8 reported a sensitivity of NIR‐ICG of 14.7%, very different from that found by Cosentino 11 and Vizzielli, 12 whose sensitivity was 82%. This inhomogeneity is difficult to interpret: in the two papers, the substantial differences concern the percentage of patients with previous surgery for endometriosis, 54% for Siegenthaler 8 and 44% in Cosentino’s work 11 and the fluorescence display time, which varies for the Siegenthaler between 2 and 20 minutes and for Cosenti between 5 and 30 minutes.…”
Section: Discussionmentioning
confidence: 78%
“…Moreover, only seven additional lesions were identified with ICG, of which only one was pathologically proven to be endometriosis. About the secondary outcome, the ICG detection rate was positively affected by the exposure time over 20 minutes, with no previous abdominal surgery and with a low rASRM 8 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations